Analisis Penyebab Perubahan APBD Provinsi Sumatera Utara - Cut Annisa Shalsabila; Kamilah Kamilah (Bursa : Jurnal Ekonomi dan Bisnis, 2022)
The purpose is to examine and explain the factors that influence budget changes as well as the role of DPRD in realizing the supervisory function in government management. This study uses a qualitative method by conducting a literature study as reference material. Data were collected through trusted news sources and related books and journals on this research topic. The results of the study show that the DPRD of North Sumatera last September 2021 agreed on the changes to the APBD which functioned as a revision of the regional budget that was adjusted to the needs that had been previously planned. This change is based on the existence of several factors behind it. And in the process of this change, of course, there are all roles of the DPRD which have a function as a supervisor in every implementation of regional autonomy, especially for the implementation of the APBD